Enhancing State Stability in New Democracies Through Political Parties - De Sousa, Adam (Université d'Ottawa | University of Ottawa, 2013)
The main goal of this paper is to highlight the need for strong political parties in new democracies. It will do so by examining why three major pillars of democracy cannot provide state stability in the short-‐term, how social cleavages and economic grievances contribute to state failure, and how several characteristics of political parties themselves enhance the chances for sustained democratic success and state stability in new democracies. It then finished up with concluding remarks.